2009
DOI: 10.1186/1471-2164-10-s1-s11
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and systems evolution in Vibrionaceae species

Abstract: Background: The steadily increasing number of prokaryotic genomes has accelerated the study of genome evolution; in particular, the availability of sets of genomes from closely related bacteria has facilitated the exploration of the mechanisms underlying genome plasticity. The family Vibrionaceae is found in the Gammaproteobacteria and is abundant in aquatic environments. Taxa from the family Vibrionaceae are diversified in their life styles; some species are free living, others are symbiotic, and others are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
(47 reference statements)
0
20
0
Order By: Relevance
“…In contrast to these examples of conservation, populations of V. cholerae and V. vulnificus maintain much more genomic diversity due, in part, to the genes captured within a super-integron locus (Chen et al, 2003;Chun et al, 2009;Boucher et al, 2011). Similarly, V. harveyi uses extensive gene duplication and fixation to diversify its genome (Gu et al, 2009). However, the most striking example of extensive evolution with a Vibrio species is the remarkably high genomic diversity reported for V. splendidus strains; even environmentally co-occurring isolates have up to 1-Mb difference in gene content from one to another (Thompson et al, 2005;Le Roux et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to these examples of conservation, populations of V. cholerae and V. vulnificus maintain much more genomic diversity due, in part, to the genes captured within a super-integron locus (Chen et al, 2003;Chun et al, 2009;Boucher et al, 2011). Similarly, V. harveyi uses extensive gene duplication and fixation to diversify its genome (Gu et al, 2009). However, the most striking example of extensive evolution with a Vibrio species is the remarkably high genomic diversity reported for V. splendidus strains; even environmentally co-occurring isolates have up to 1-Mb difference in gene content from one to another (Thompson et al, 2005;Le Roux et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…(Gu et al, 2009). However, around 200 genes, found in 41 loci comprising two or more adjacent orfs, are present only in the genomes of D-type strains.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis by BLAST revealed that sequences homologous to VC1372 are found only in a few Vibrio species, dominated by strains of V. cholerae. A previous study has also noted that VC1372 is unique to V. cholerae among members of the genus Vibrio (72).…”
Section: Discussionmentioning
confidence: 99%
“…Gene duplication and lateral gene transfer (LGT) are believed to be major evolutionary forces driving the genome evolution in bacteria [7-9]. Gene duplication is of paramount importance for functional innovation.…”
Section: Introductionmentioning
confidence: 99%